Factors increasing the risk for a severe reaction in anaphylaxis: An analysis of data from The European Anaphylaxis Registry. Issue 6 (8th March 2018) - Worm, M.; Francuzik, W.; Renaudin, J.‐M.; Bilo, M. B.; Cardona, V.; Scherer Hofmeier, K.; Köhli, A.; Bauer, A.; Christoff, G.; Cichocka‐Jarosz, E.; Hawranek, T.; Hourihane, J. O.'B.; et al.
Abstract: Background: Preventive measures to decrease the frequency and intensity of anaphylactic events are essential to provide optimal care for allergic patients. Aggravating factors may trigger or increase the severity of anaphylaxis and therefore need to be recognized and avoided. Objective: To identify and prioritize factors associated with an increased risk of developing severe anaphylaxis. Methods: Data from the Anaphylaxis Registry (122 centers in 11 European countries) were used in logistic regression models considering existing severity grading systems, elicitors, and symptoms to identify the relative risk of factors on the severity of anaphylaxis. Results: We identified higher age and concomitant mastocytosis (OR: 3.1, CI: 2.6‐3.7) as the most important predictors for an increased risk of severe anaphylaxis. Vigorous physical exercise (OR: 1.5, CI: 1.3‐1.7), male sex (OR: 1.2, CI: 1.1‐1.3), and psychological burden (OR: 1.4, CI: 1.2‐1.6) were more often associated with severe reactions. Additionally, intake of beta‐blockers (OR: 1.9, CI: 1.5‐2.2) and ACE‐I (OR: 1.28, CI: 1.05, 1.51) in temporal proximity to allergen exposition was identified as an important factor in logistic regression analysis. Conclusion: Our data suggest it may be possible to identify patients who require intensified preventive measures due to their relatively higher risk for severe anaphylaxis by considering endogenous and exogenous factors.